Assessment of Human-Elephant Conflicts, Vulnerabilities and Sustainable Mitigation Approaches in Omkar and Kundakere Ranges of Bandipur National Park - Shivaraju H. P. (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Human-elephant conflict impact is upon the wellbeing of the people and their assets worldwide. Conservation of wildlife has been a big challenge in human dominated landscapes as they frequently come into conflict with humans. It is one of the major threats for long-term survival species of wildlife and land use patterns of the region. Human-elephant conflict data was collected during 2014–2015 at Omkar and Kundakere ranges of Bandipur National Park by following the standard survey techniques. Information about conflict area, conflict reasons, its vulnerabilities, habitation, land use patterns and current mitigation methods were collected from 60 pre-identified informants. A GIS technique was used for coordination of forest boundary, conflict zones and severity of conflicts around the study sites. More than 180 incidents of conflicts were reported within Omkar and Kundakere ranges with a high intensity. Crop damage was reported as the most common and frequent impact along with the death of humans and elephants. About 95% of respondents have the perception that human-elephant conflict has increased gradually from the last three years due to destruction of natural habitat, encroachment, crop pattern and other natural calamities like drought and uncertain diseases in forest plants. A significant number of human-elephant conflicts were reported only in Omkar and Kundakere ranges when compared to other ranges of the reserve forest. This is due to location of this region towards human habitats with severe fragmentation and encroachment of elephant corridor and natural habitats. In addition to that, severe deforestation, location of peripheral highways and agricultural land and failure of elephant ride barrier in these ranges were the reasons for frequent conflicts and impacts between humans and elephants.